Gender order and sisterhood in Ai wei’s fictions - Tan, Ching Ching (2019)
The thesis consists of two parts. The first is about gender order. The second is sisterhood. For gender order, it is divided into two types. One is female self- construction, another one is female parent’s construction. The traditional society implemented patriarchy which regarded female as secondary. The first part of thesis emphasizes the ways of female to deconstruct their second class status and build up self-construction so that to enhance their pride and society status. For female self-construction, there were some methods such as fought against the patriarchy, pursued love, pursued building up good character and pursued achievements. Besides, the author tried to construct female’s parent by making the male parents absent from the family, or gave them despicable character. The above reasons caused them losing their rights in the family. As a result, the female parent automatically took over the family administration right. The exist of female parent in the family implied that the female got rights to fight against the female second role in the patriarchy. For sisterhood, it emphasizes the sincere feeling among female relatives and friends. In relationship of mother and daughter, the mothers always showed caring, love to their daughters. Besides, they also hoped their daughters get happy marriage. Another point is the caring happened among the female friends and general ladies. The good friends always showed caring and consoled their female friends whom were in depression or encountered difficulties. The latter mostly showed their caring based on female sympathies. For research method, close reading is the basic of research. The analysis of thesis is also based on summarizing and comparing of texts. In general, the research is conducted through combination of feminist theory and author’s perception of the topic and other related methodologies.